'A Reduced Consciousness': Subjective Experience and the Restoration of Community in the Late Works of Saul Bellow. - Gallivan, Euan (2006)
This essay explores the recurring predicament in Saul Bellow's fiction of the individual who, either through an aspiration to greatness or an over-reliance on the rational intellect, becomes alienated from human community. Adrift in a culture in which personal relationships are constantly being eroded, the Bellovian protagonist's estrangement is variously exacerbated by the decline of the modern city; the disintegration of the family and of loving relationships; and of a 'discourse of confusion' propounded by the media, all of which derive in some way from the contemporary prominence of theoretical, objectivist discourse. Although his characters are often portrayed as being complicit in the proliferation of such discourse, Bellow's works all deal with the attempt to reassert the importance of subjective thought and thereby re-establish human community. It is my assertion that although the recurrence of such concerns confers a sense of thematic consistency upon Bellow's canon, they are particularly relevant to the works of his post-Nobel period. As such, the essay deals primarily with the novels The Dean's December (1982), More Die of Heartbreak (1987) and Ravelstein (2000), as well as the novellas The Bellarosa Connection (1989), A Theft (1989) and The Actual (1997).